Intertextuality of Balinese Writers Works in Comprehending Tradition (A Reinterpretation, Reconstruction, and Cultural Response) - Artawan, Gde (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2017)
This study aims at finding intertextuality of Balinese writersâ works in reinterpreting culture, finding intertextuality of Balinese writersâ works in comprehending tradition. Sociologically, the works of those three writers were reviewed to know the narrative construction...